A Storm is Coming? Collective Sensemaking and Ambiguity in an Inter-organizational Team Managing Railway System Disruptions. Issue 3 (3rd July 2017) - Merkus, Sander; Willems, Thijs; Schipper, Danny; van Marrewijk, Alfons; Koppenjan, Joop; Veenswijk, Marcel; Bakker, Hans
ABSTRACT: This paper studies the ways in which members of inter-organizational teams collectively make sense of unexpected events and how they decide upon engaging in action. Frequently, ambiguity dominates such change processes aimed to create common understanding. Using the notion of the duality of intrinsic and constructed ambiguity, a detailed analysis of the collective sensemaking efforts of an inter-organizational team of railway coordinators in the Operational Control Center Rail was conducted. Building on team meetings observations during the days preceding a large and potentially disruptive winter storm in December 2013, the case study describes the process of collectively making sense of the disruptiveness of the storm. The findings show that contextual and temporal factors determine whether collective sensemaking unfolds as either a shared or a negotiated process.